Life Style Factors Influencing Serum Pepsinogen Levels in Healthy Japanese: A Prospective Study - Murdani Abdullah; Fumiaki Kitahara; Tadashi Sato; Yuichiro Kojima; Abdul Aziz Rani; Masayuki A. Fujino (The Indonesian Society for Digestive Endoscopy, 2003)
Background: Gastric cancer mass screening using serum pepsinogen has been recognized and several advantages of this methods over photofluorography have been shown by previous study. Aims: To determine the factors influence the serum pepsinogen levels in healthy subjects. Subjects Methods: One thousand and one hundred fourteen subjects who were screened for gastric cancer as part of a periodic health check. Blood samples were taken after fasting and stored below –20 ° C, until pepsinogen levels were assayed. Results: The subjects consist of 338 males (mean age 52.6+14.0) and 776 females (mean age 49.0+11.9). Age ranges from 19 to 81 years. The overall prevalence of chronic atrophic gastritis using a criterion PG I £ 70 hg/ml and PG I/II ratio £ 3.0 was 21.99 % in 1996 and 23.97 % in 2000. Bivariate analysis revealed a significant association between age, more salt consumption, fish favorable over meat and less than three time meal intake covariates with the lowering of PG I/II ratio. Smoking, drinking, BMI, weight and gender did not affect the changes of PG I/II ratio. Conclusion: Age and more salt consumption covariates have a strongest association with the decreased of PG I/II by multivariate analysis. Keywords: pepsinogen, dietary, drinking, smoking, atrophic gastritis